1994
DOI: 10.1093/amt/19.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insecticide and Insecticide Combinations for Beet Armyworm Control, 1993

Abstract: Fifteen insecticide treatments were evaluated for efficacy on cotton located in Attala county, MS, on the Weldon Harris farm. Cotton was planted in a 2-1 skip pattern and plots were 6 rows wide × 50 ft long. A RCBD with 3 replications was used. Applications were made 24 Aug with a high clearance spray tractor equipped with a compressed air spray system with TX4 hollow cone nozzles spaced at 19 inches and positioned approximately 16 inches above the terminals. Applications were made at 4 mph with the system cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In South Carolina, thiodicarb also provided 90% control of beet armyworm in cotton (Sullivan et al 1991). Reed et al (1994) reported <50% control of beet armyworm with both thiodicarb and chlorpyrifos in Mississippi cotton. In Louisiana, control of beet armyworm with thiodicarb and chlorpyrifos in cotton has been inconsistent (Burris et al 1994;Graves et al 1995;Mascarenhas et al 1996).…”
Section: R Esumenmentioning
confidence: 99%
“…In South Carolina, thiodicarb also provided 90% control of beet armyworm in cotton (Sullivan et al 1991). Reed et al (1994) reported <50% control of beet armyworm with both thiodicarb and chlorpyrifos in Mississippi cotton. In Louisiana, control of beet armyworm with thiodicarb and chlorpyrifos in cotton has been inconsistent (Burris et al 1994;Graves et al 1995;Mascarenhas et al 1996).…”
Section: R Esumenmentioning
confidence: 99%